Understanding users' continuous content contribution behaviours on microblogs: an integrated perspective of uses and gratification theory and social influence theory. Issue 5 (3rd May 2020) - Liu, Xiaodan; Min, Qingfei; Han, Shengnan
ABSTRACT: Microblogs are revolutionising the way users produce, consume and distribute short content. The continuous content contributions of users are crucial for the sustainable development of microblogs. Knowledge regarding this user behaviour is scarce. Based on the uses and gratifications theory (U&G) and the social influence theory (SIT), this paper proposes an integrated research model with the aim of understanding the factors that affect users' continuous content contribution behaviours (CCCB) on microblogs. The data were collected from 379 microblog users in China. The empirical results indicate that perceived gratification had a positive but surprisingly trivial effect on continuous content contribution behaviours. Social influence had a strong and significantly positive effect on users' CCCB, it also had a positive moderating effect on the relationship between perceived gratification and CCCB. Users' perceived gratification was positively affected by the antecedents of self-expression, anticipated extrinsic rewards and anticipated reciprocity but negatively affected by privacy concerns. The platform attributes of microblogs (i.e. accessibility and interactivity) also influenced users' perceived gratification. This research contributes to social media research with regards to the theory of users' CCCB.